2014
DOI: 10.1021/jp412041d
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Binding of Cyclodextrin Dimers to Isoflavone Analogues Elucidated by Free Energy Calculations

Abstract: Dimerization of cyclodextrin (CD) molecules is an elementary step in the construction of CD-based nanostructured materials. Cooperative binding of CD cavities to guest molecules facilitates the dimerization process and, consequently, the overall stability and assembly of CD nanostructures. In the present study, all three dimerization modes (head-to-head, head-to-tail, and tail-to-tail) of β-CD molecules and their binding to three isoflavone drug analogues (puerarin, daidzin, and daidzein) were investigated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 79 publications
0
47
0
2
Order By: Relevance
“…It was demonstrated that the cooperative binding of CD cavities to guest molecules favors the dimerization process and, consequently, the overall stability and assembly of the CD nanostructures. It was also proved that the desolvation of CD dimers and entropy changes upon complexation cooperatively contributes to the binding process [78].…”
Section: Computational Observationsmentioning
confidence: 96%
See 2 more Smart Citations
“…It was demonstrated that the cooperative binding of CD cavities to guest molecules favors the dimerization process and, consequently, the overall stability and assembly of the CD nanostructures. It was also proved that the desolvation of CD dimers and entropy changes upon complexation cooperatively contributes to the binding process [78].…”
Section: Computational Observationsmentioning
confidence: 96%
“…Computer simulations have been used to rationalize the experimental findings concerning recognition [77], inclusion [36,[77][78][79], and aggregation [34,35,37,39,80]. The cooperative binding of at least two CD monomers to a guest molecule has been considered the driving force responsible for self-assembly processes in the construction of CD-based nanoarchitectures [78].…”
Section: Computational Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of the estimated binding free-energy depends on the correct estimation of thermodynamic quantities and the concerted interaction components (enthalpy, entropy and solvent contributions) [15,47]. For instance, the quantification of these interaction components have been directed at inclusion complexes between cyclodextrins and its derivatives and different model drugs (see Refs.…”
Section: Context and Relevant Aspectsmentioning
confidence: 99%
“…20) with the CHARMM 36 force eld. 23,24 However, owing to possible inconsistencies between the CHARMM36 and the q4md-CD force elds-arising from distinct parameterization philosophies, the CHARMM force eld for carbohydrates, 25,26 which has proven suitable for the study of CDs, 19,21 was employed in this work to describe the pyranose monosaccharides and glycosidic linkages of the altro-a-CD. 21 The q4md-CD force eld, 22 an Amber-derived force eld, has been shown to perform remarkably well for the modeling of CDs.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%